Assessment of relative dispersion in the Gulf of Tonkin using numerical modeling and HF radar observations of surface currents. (1st August 2022) - Tran, Manh Cuong; Sentchev, Alexei; Berti, Stefano; Ayoub, Nadia K.; Nguyen-Duy, Tung; Cuong, Nguyen Kim
Abstract: Particle pair statistics from synthetic drifter trajectories reconstructed from realistic, high-resolution numerical simulations (SYMPHONIE model) and HF radar velocity measurements are used to investigate the dispersion properties in the Gulf of Tonkin (GoT). This study takes an approach based on two-particles statistics providing the relative dispersion, relative diffusivity and Finite Size Lyapunov Exponent (FSLE) estimates. In the GoT, the relative dispersion follows the predictions from the theory of two-dimensional turbulence with two inertial subranges identified in the kinetic energy spectrum with the spectral slopes −5/3 and −3. The time evolution of dispersion shows an exponential growth during 5–8 days, followed by a power law regime during the next 6–20 days. Fixed-length indicators from the relative diffusivity and the FSLE reveal a local dispersion at large and intermediate scales (above Rossby radius of deformation) and non-local dispersion in sub-mesoscale range (below Rossby radius of deformation). The effect of river runoff on the local hydrodynamics and dispersion processes is assessed using the numerical model simulations without river discharge. The results show that in the model, the river plume, when present, highly impacts the Lagrangian statistics. High gradients of buoyancy reinforce the sub-mesoscale circulation in a large region along the Vietnamese coast and modify the scales and intensity of turbulent dispersion. However, a clear change of dispersion regime in the sub-mesoscale range is not identified, suggesting that the mesoscale circulation in the GoT largely governs particle spreading even at small scale. Highlights: Relative dispersion in the Gulf of Tonkin is assessed using the synthetic drifters advected in the velocity field from high-resolution numerical model and HF radar. Seasonal variability in transport patterns and dispersion regimes are characterized. A seasonality in dispersion rate is related to seasonal variations of wind and freshwater input into the gulf. Four regions of high-level of dispersion are identified in the Gulf of Tonkin on the basis of FSLE maps.